Digitising Folktales for Animation and Value Education - Igboho Field Location Video - Yusuff, Ayodele; Eleshin, Abisoye (Regenerating Non-Formal Learning in Africa: Digitizing Yoruba Folktales for Animation and Value Education, 2021)
Video recording from Igboho, Oyo State, Nigeria
Keywords: Learning; Animation (Cinematography); Children; Child psychology; Curriculum planning; African Studies; Tortoise